Effect of Different Levels of Sunflower Seed in Broiler Rations - Suchon Tangtaweewipat; Boonlom Cheva-Isarakul (Agriculture and Natural Resources, 1990)
The study on the utilization of various levels of sunflower seed ( SFS ) in broiler diets was carried out in 2 experiments, each lasted 7 weeks. Experimental diets contained 21, 19 and 17 % CP for birds aged 1-3, 3-6 and 6-7 week, respectively. Metabolizable energy was allowed to variate according to the level of SFS. In experiment 1, eight hundred fourty heads of straight run Hubbard broiler were randomly allocated to 7 groups, each with 4 replicates. The first 5 groups were fed with diets containing 0, 15, 20, 25 and 30% SFS throughout the experiment, while the last 2 groups 0 and 10% SFS were fed during the first period ( 1-3 week of age ) and 30 and 30 % SFS during week 3-7. In experiment 2, eight hundred and ten heads of straight run AA 707 broiler were randomly allocated to 9 groups, each with 3 replicates. They were fed with 0, 30, 40 or 50% SFS throughout the experiment or 50% SFS during the first period and 30% in the last period ( week 3-7 ). At each level of SFS, the diets were either adjusted for lysine ( group 3, 5, 7, 9 ) to be equal to the control ( 0% SFS, gr 1 ) or unadjusted ( group 2, 4, 6, 8 ), in which lysine was supplemented at the same level with the control. The results from both experiments indicated that birds fed with SFS diets tend to gain slightly more weight ( 1.6 – 7.1% ) than the control. Feed consumption decreased with the increasing level of SFS, which consequently improved FCR significantly. Liver an d Pancreas weight decreased, while abdominal plus visceral fat increased with SFS level. No significant differences among groups was found on mortality rate, haematocrit, haemoglobin, as well as serum cholesterol level. Neither production performance nor blood parameters was affected by lysine level in the diets.